Dekyphosis operation combined with limited osteotomy to treat the symptomatic adult tethered cord syndrome with complicated malformations: A case report. Issue 17 (28th April 2023) - Jiao, Liang; Yang, Xiao; Wang, Shuang; Ma, Jun-Xiong; Zheng, Liang; Wang, Hong; Yu, Hai-Long; Chen, Yu
Abstract : Rationale: Tethered cord syndrome (TCS) represents a spectrum of neurological symptoms that are caused by constant or intermittent axial traction of the terminal cone of the spinal cord due to abnormal positioning. It is uncommon for abnormal structures of TCS to be accompanied by split cord malformation, thoracic spinal stenosis, and other spinal cord diseases. Patient concerns: A 45-year-old male patient visited our hospital due to severe lower back pain, extensive left lower limb muscle weakness, and intermittent claudication. Diagnoses: TCS combined with stenosis of the thoracic canal, split cord malformation, and kyphosis deformity. Interventions: The patient underwent Dekyphosis operation combined with limited osteotomy symptoms. Outcomes: The patient felt the right lower limb improved after surgery. At 4-month follow-up, a radiological examination showed adequate decompression of the spinal cord and a good internal fixation position. Overall, the patient's clinical symptoms significantly improved. Conclusion: This is a rare case of TCS combined with thoracic disc herniation and bony mediastinum. A more conservative invasive surgical approach was elected and markedly improved the patient's symptoms. Additional clinical cases are needed to confirm the stability and feasibility of this surgical approach.